Comparative study on liquefaction behaviors of xylan hemicellulose as treated by different hydrothermal methods - Natthanon Phaiboonsilpa; Verawat Champreda; Navadol Laosiripojana (Energy Reports, 2020)
Liquefaction behaviors of xylan were studied as treated by six different hydrothermal methods. As a comparative study, a xylan sample isolated from corn core was subjected to hot-compressed water, hot-compressed 0.01 and 0.1wt% HO2 solutions under pressurization of N or CO2 at 110-250 °C for 0 min in 10-ml batch-type reactor. Not only xylose and xylo-oligosaccharides, but also arabinose, glucose, and acetic acid were recovered as hydrolyzed products. In addition, decomposition compounds, i.e. furans and organic acids were found. The highest xylose yield could be attained at 210 °C in all the studied hydrothermal methods, except for only 0.1wt% HO2 solution under pressurization of CO2. By this strongly oxidative condition, where peroxy carbonic acid was formed in situ, the temperature that xylose could be highly recovered was at 190 °C. The highest xylose yield of 61.62wt% was obtained by 0.01wt% HO2 solution under pressurization of N. Formation of furan compounds showed a preference to the treatments with pressurized CO2, while organic acids had a better recovery when N was applied. Different results in the production of various liquefied products could be attributed to the degree of hydrolysis and oxidation reactions which altered under the different hydrothermal methods.
Keywords: 330; Carbon dioxide; Hemicellulose; Hydrogen peroxide; Hydrolysis; Liquefaction; Oxidation; Xylan